\(\dfrac{2}{7}-\dfrac{1}{3}=\dfrac{6}{21}-\dfrac{7}{21}=-\dfrac{1}{21}\)
\(\dfrac{2}{7}-\dfrac{1}{3}\) = \(\dfrac{6}{21}-\dfrac{7}{21}\) = \(\dfrac{-1}{21}\)
\(\dfrac{2}{7}-\dfrac{1}{3}=\dfrac{6}{21}-\dfrac{7}{21}=-\dfrac{1}{21}\)
\(\dfrac{2}{7}-\dfrac{1}{3}\) = \(\dfrac{6}{21}-\dfrac{7}{21}\) = \(\dfrac{-1}{21}\)
Tính nhanh :
\(C=\dfrac{1}{3}+\dfrac{-3}{4}+\dfrac{3}{5}+\dfrac{1}{57}+\dfrac{-1}{36}+\dfrac{1}{15}+\dfrac{-2}{9}\)
\(D=\dfrac{1}{2}+\dfrac{-1}{5}+\dfrac{-5}{7}+\dfrac{1}{6}+\dfrac{-3}{35}+\dfrac{1}{3}+\dfrac{1}{41}\)
\(E=\dfrac{-1}{2}+\dfrac{3}{5}+\dfrac{-1}{9}+\dfrac{1}{127}+\dfrac{-7}{18}+\dfrac{4}{35}+\dfrac{2}{7}\)
a) \(\dfrac{\left(3+\dfrac{1}{6}\right)-\dfrac{2}{5}}{\left(5-\dfrac{1}{6}\right)+\dfrac{7}{10}}\)
b) \(\dfrac{\left(4,08-\dfrac{2}{25}\right):\dfrac{4}{17}}{\left(6\dfrac{5}{9}-3\dfrac{1}{4}\right).2\dfrac{2}{7}}\)
c) \(\dfrac{2-\dfrac{1}{4}+\dfrac{1}{3}-\dfrac{3}{5}}{3-\dfrac{1}{5}-\dfrac{5}{3}}\)
\(\dfrac{-3}{4}\) + \(\dfrac{2}{7}\) + \(\dfrac{-1}{4}\) +\(\dfrac{3}{5}\) +\(\dfrac{5}{7}\)
tính
\(G=\left(1-\dfrac{1}{7}\right)\left(1-\dfrac{2}{7}\right)\left(1-\dfrac{3}{7}\right)...\left(1-1\dfrac{2}{7}\right)\left(1-1\dfrac{3}{7}\right)\)
\(\dfrac{\dfrac{3}{7}-\dfrac{3}{11}+\dfrac{3}{13}}{\dfrac{5}{7}-\dfrac{5}{11}+\dfrac{5}{13}}+\dfrac{\dfrac{1}{2}-\dfrac{1}{3}+\dfrac{1}{4}}{\dfrac{5}{4}-\dfrac{5}{6}+\dfrac{5}{8}}\)
THỰC HIỆN PHÉP TÍNH NHA MN
\(B=\left(\dfrac{0,4-\dfrac{2}{9}+\dfrac{2}{11}}{1,4-\dfrac{7}{9}+\dfrac{7}{11}}-\dfrac{\dfrac{1}{3}-0,25+\dfrac{1}{5}}{1^1_6-0,875+0,7}\right).\dfrac{1842009}{1842010}\)
75%:2\(\dfrac{1}{5}\)+(0,5)2.(-7)+2,5(7\(\dfrac{2}{3}\)+5\(\dfrac{2}{3}\))
SS A và B
A=\(\dfrac{19}{24}-\dfrac{1}{2}-\dfrac{1}{3}-\dfrac{7}{24}\)
B=\(\dfrac{7}{24}+\dfrac{5}{6}+\dfrac{1}{4}-\dfrac{3}{7}-\dfrac{5}{15}\)
CMR : \(\dfrac{2}{5}< A< \dfrac{8}{9}\)
Với \(A=\dfrac{1}{2^2}+\dfrac{1}{3^2}+\dfrac{1}{4^2}+\dfrac{1}{5^2}+\dfrac{1}{6^2}+\dfrac{1}{7^2}+\dfrac{1}{8^2}+\dfrac{1}{9^2}\)
\(\text{Thực hiện phép tính một cách hợp lý nhất (nếu có thể):}\)
\(1\)) \(\left(\dfrac{-8}{13}:\dfrac{3}{7}+\dfrac{-5}{13}:\dfrac{3}{7}\right).\dfrac{\left(-4\right)^3.\left|-3\right|}{7}\)
\(2\)) \(75\)\(\text{%}\)\(-\left(\dfrac{5}{2}+\dfrac{5}{3}\right)+\left(-\dfrac{1}{2}\right)^2\)